(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fog Computing is a region of Computer Science that is under steady construction and development, and related to data security, the worldview turns out to be more solid and secure for IoT’s edge stages. The verification of limited memory devices has serious issues since memory utilization is high when applied with different models that have the motivation behind shared confirmation. In this paper, we propose the Novel cipher text-based encryption model (NCEM) which has an information access control plot dependent on Ciphertext-Policy it give information privacy, fine-grained control, and mysterious validation in a multi-authority fog computing framework. The sign cryption and plan cryption overhead for the client is altogether diminished by redistributing the bothersome calculation tasks to fog hubs. The proposed conspire is demonstrated to be secure in the standard model and can give trait repudiation and public unquestionable status. The security analysis, asymptotic multifaceted nature examination, and implementation results demonstrate that our construction can offset the security objectives with useful effectiveness in calculation.